Searching for the microcosm: a glimpse into the roots of Vygotsky’s holism - Cornejo, Carlos (History of the human sciences, 2015)
In this article, I examine Vygotsky’s holism by considering his usage of ‘microcosm’ and chronicling the term’s origin and development. This exploration leads first to Spinoza’s monism as the primordial source of Vygotsky’s holism. Then, I present the notion of microcosm in the context of German Romanticism and J. W. Goethe. Humboldt’s Cosmos and Lotze’s Microcosmus are presented as 19th-century exemplars of the holistic tradition. Finally, I examine Vygotsky’s usage of the term ‘microcosm’ and argue that this concept cannot be fully understood outside the long tradition of holism in western philosophy. This understanding helps to explain apparent contradictions in his texts as well as affinities with his contemporaries’ philosophy of life and German holistic approaches.
Gesehen am 08.12.2020